2017
DOI: 10.7717/peerj.3030
|View full text |Cite
|
Sign up to set email alerts
|

New in vitro system to predict chemotherapeutic efficacy of drug combinations in fresh tumor samples

Abstract: BackgroundTo find the best individual chemotherapy for cancer patients, the efficacy of different chemotherapeutic drugs can be predicted by pretesting tumor samples in vitro via the chemotherapy-resistance (CTR)-Test®. Although drug combinations are widely used among cancer therapy, so far only single drugs are tested by this and other tests. However, several first line chemotherapies are combining two or more chemotherapeutics, leading to the necessity of drug combination testing methods.MethodsWe establishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Serendipitous discovery in the clinic has been a traditional source of effective drug combinations 5,6 . Yet systematic large-scale efforts to identify them have only recently been pursued, with a growing number of preclinical experimental efforts to identify synergistic combinations [6][7][8][9][10][11] being reported in literature. The sheer number of available and possible drug-like molecules 12 and an exponential number of their combinations, however, make the process of finding new therapeutic combinations by purely experimental means highly inefficient.…”
Section: Introductionmentioning
confidence: 99%
“…Serendipitous discovery in the clinic has been a traditional source of effective drug combinations 5,6 . Yet systematic large-scale efforts to identify them have only recently been pursued, with a growing number of preclinical experimental efforts to identify synergistic combinations [6][7][8][9][10][11] being reported in literature. The sheer number of available and possible drug-like molecules 12 and an exponential number of their combinations, however, make the process of finding new therapeutic combinations by purely experimental means highly inefficient.…”
Section: Introductionmentioning
confidence: 99%
“…We added the two scores of the single measurements to obtain the score and the resistance class of the combination. We recently published a paper where we described an in vitro system to predict the chemotherapeutic efficacy of drug combinations [ 15 ]. With this system it is possible to use single measurements to predict the efficacy of drug combinations in certain cases and to measure combinations directly.…”
Section: Discussionmentioning
confidence: 99%
“…Soft agar matrix (0.4%) selective for tumor growth was placed in 24-well polystyrene culture dishes and 50 μl of one specific chemotherapeutic drug was then added to appropriate wells. The drug concentrations can be found in [ 15 ]. Tumor cells suspended in 0.5 ml tissue culture medium and 0.2% agarose were then added to each well.…”
Section: Methodsmentioning
confidence: 99%
“…Serendipitous discovery in the clinic has been a traditional source of effective drug combinations (Zoli et al, 2001; Kurtz et al, 2015). Yet systematic large-scale efforts to identify them have only recently been pursued, with a growing number of preclinical experimental efforts to identify synergistic combinations (Zoli et al, 2001; Budman et al, 2012; Lieu et al, 2013; Kashif et al, 2015; Yu et al, 2015; Kischkel et al, 2017) being reported in literature. The sheer number of available and possible drug-like molecules (Polishchuk et al, 2013) and an exponential number of their combinations, however, make the process of finding new therapeutic combinations by purely experimental means highly inefficient.…”
Section: Introductionmentioning
confidence: 99%